How Nova Scotia General Practitioners Choose Antibiotics for the Empirical Treatment of Community-Acquired Pneumonia - Jacob Pendergrast; Thomas J Marrie (Canadian Journal of Infectious Diseases)
OBJECTIVE: To gain an understanding of how physicians in general practice choose antibiotics for the empirical treatment of community-acquired pneumonia (CAP).